Irene Street, San Jose
Aerial photograph of Irene Street in San Jose, 1953. The photograph is oriented from west to east along the vertical axis and north to south along the horizontal. Irene Street is the horizontal street, with Village Court above and Asbury Street below. Emory Street can be seen on the far left, and the Guadalupe River follows the tree line.